Nonlinear rheological behavior and quantitative proteomic analysis of pea protein isolates at the air-water interface. (February 2023) - Shen, Qian; Luo, Yilun; Zheng, Wei; Xiong, Ting; Han, Fei; Zuo, Jingnan; Dai, Jun; Li, Bin; Chen, Yijie
Abstract: In this study, the pea protein isolate (PPI) and its three major components (legumin, vicilin, and albumin) stabilized protein foams were analyzed. The results of foaming capacity and foam stability showed that the foam with more compact interfacial protein film possessed a better foam capacity. The result also showed that, comparing with the legumin component, the lower half-life time of PPI-stabilized foam may be due to the increase of albumins in interfacial protein layer which was quantified by quantitative proteomics, for our results showed that albumins possessed poor foam stability. Further, the interfacial rheological properties of the three major components at the air-water interface were investigated by the nonlinear rheological response in the high-amplitude regime (10%–30%). The rearrangement rate (kR ) of vicilin was significantly higher than that of the other components, suggesting a more apparent protein rearrangement occurred at the air-water interface. The albumin stabilized air-water interface was little elasticity and stiffness, which may lead to the poor foam stability. In the study, the air-water interfacial proteins and their properties of PPI-stabilized foam were investigated by their macroscopic properties, quantitative proteomics and interfacial properties, which could reveal the underlying interfacial protein quantity-structure-property relationship of the protein foam. Graphical abstract: Image 1 Highlights: Albumins in PPI could decrease the PPI-stabilized foam half-life time. The quantities of air-water interfacial albumins increased after 30 min adsorption. The nonlinear rheological behavior of PPI components was related with foam stability.